2015
DOI: 10.1007/s00214-015-1681-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of internal molecular dynamics on the evaporation/condensation of n-dodecane

Abstract: The effects of conformerisation and internal molecular dynamics (IMD) of n-dodecane conformers on energy transfers between gas and liquid phases are investigated. Bond energies, Gibbs free energies of internal dynamics of a set of n-dodecane conformers, and energies of the molecules colliding with the surface of an n-dodecane nanodroplet are studied using quantum chemical calculations (DFT with B97X-D/cc-pVTZ and semi-empirical PM7) and ReaxFF method. The results of the analysis show that the accuracy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A non-equilibrium MD simulation technique using ReaxFF is proposed to determine thermal evaporation coefficient of n -dodecane, a representative of n -alkanes in Diesel fuel. The reliability of reactive force field ReaxFF has also been assessed and compared for modeling the evaporation of hydrocarbons 15 using the quantum chemical calculations (DFT and PM7 methods) and available experimental data on the determination of bond energies, Gibbs free energies of internal molecular dynamics of a set of n -dodecane conformers and collision energies of attacking molecules with the surface of the droplet. It was shown that ReaxFF performs better than semi-empirical quantum chemistry PM7 method in terms of both cost and accuracy of calculations of the evaporation of n -dodecane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A non-equilibrium MD simulation technique using ReaxFF is proposed to determine thermal evaporation coefficient of n -dodecane, a representative of n -alkanes in Diesel fuel. The reliability of reactive force field ReaxFF has also been assessed and compared for modeling the evaporation of hydrocarbons 15 using the quantum chemical calculations (DFT and PM7 methods) and available experimental data on the determination of bond energies, Gibbs free energies of internal molecular dynamics of a set of n -dodecane conformers and collision energies of attacking molecules with the surface of the droplet. It was shown that ReaxFF performs better than semi-empirical quantum chemistry PM7 method in terms of both cost and accuracy of calculations of the evaporation of n -dodecane.…”
Section: Resultsmentioning
confidence: 99%
“…SAFT can be applied for predicting interfacial layer thickness of fluids and it incorporates the effects of chain length, molecular association and other interactions such as long-range dipolar forces and dispersions. While the interfacial layer effects were not explicitly modelled in refs 9 , 13 , 15 and 16 , we consider these effects in this study by setting up an equation including interfacial width, δ. A standard state has to be defined for the evaporation/condensation process and with this thickness the relationship between the free energy of evaporation/condensation (ΔG g↔int ) and the coefficient β m becomes: where <Δ G g↔int > presents the average difference values of Gibbs free energy of conformers in the interfacial layer and gas phase (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in one study, n -dodecane molecules had mostly orientation parallel to the surface 11 , in 13 the authors claim that n -decane (C 10 H 22 ), n -tetracosane (C 24 H 50 ) and n -hexatriacontane (C 36 H 74 ) molecules have random orientation (both parallel and normal to surface) at the interface. While the FF predicted that all-trans conformer of n -hexadecane are dominated in the liquid phase over the other conformers 14 , quantum mechanical solvation results shown that n -dodecane with all-trans conformer cannot exist in the liquid phase 10 .…”
mentioning
confidence: 95%
“…The reliability of the FF approach becomes particularly questionable for molecules with multiple conformers especially at the interface and extreme conditions such as internal combustion engine-like conditions (e.g., high temperatures and pressures). This deficiency in FFs in such a situation is related to the fact that the internal rotations or torsions of long chain molecules are parameterized using FFs based on a single conformer, while characterizations of these sorts of internal molecular dynamics in the hydrocarbon molecules, the main components of fuel droplets, with multi-structural effects change from one another 10 . This is supported by the results obtained for orientation of n -alkanes at the centre of interfacial layer using non-reactive MD simulations and experimental results 11 12 13 .…”
mentioning
confidence: 99%